Corruption, the Rusiness Environment, and Small Business Growth in India - Honorati, Maddalena; Mengistae, Taye (World Bank, Washington, DC, 2012)
This paper estimates a dynamic business growth equation on a sample of small-scale manufacturers. The results suggest that excessive labor regulation, power shortages, and problems of access to finance are significant influences on industrial growth in India. The expected annual sales growth rate of an enterprise is lower where labor regulation is greater, power shortages are more severe, and cash flow constraints are stronger. The effects of each of the three factors on business growth seem also to depend on a fourth element, namely, corruption. Specifically, labor regulation affects the growth only of enterprises for which corruption is not a factor in business decisions. By contrast, power shortages seem to be a drag on the growth only of enterprises self-reportedly held back by corruption. Lastly, sales growth is constrained by cash flow only in businesses that are not affected by labor regulation, power shortages, or corruption. The analysis uses corruption as a proxy for the quality of "property rights institutions" and considers labor regulation and small business financing as instances of "contracting institutions." The findings on the interaction between corruption and other aspects of business environment then seems to indicate that the quality of property rights institutions exerts more abiding influence on economic outcomes than the quality of contracting institutions. Moreover, there might also be a hierarchy among contracting institutions in their effect on manufacturing growth.